Common elements in interleukin 4 and insulin signaling pathways in factor-dependent hematopoietic cells. - Wang, L M (1993)
Interleukin 4 (IL-4), insulin, and insulin-like growth factor I (IGF-I) efficiently induced DNA synthesis in the IL-3-dependent murine myeloid cell lines FDC-P1 and FDC-P2. Although these factors could not individually sustain long-term growth of these lines, a combination of IL-4 with either insulin or IGF-I did support continuous growth. The principal tyrosine-phosphorylated substrate observed in FDC cells stimulated with IL-4, previously designated 4PS, was of the same size (170 kDa) as the major substrate phosphorylated in response to insulin or IGF-I. These substrates had phosphopeptides of the same size when analyzed by digestion with Staphylococcus aureus V8 protease, and each tightly associated with the 85-kDa component of phosphatidylinositol 3-kinase after factor stimulation. IRS-1, the principal substrate phosphorylated in response to insulin or IGF-I stimulation in nonhematopoietic cells, is similar in size to 4PS. However, anti-IRS-1 antibodies failed to efficiently precipitate 4PS, and some phosphopeptides generated by V8 protease digestion of IRS-1 were distinct in size from the phosphopeptides of 4PS. Nevertheless, IL-4, insulin, and IGF-I were capable of stimulating tyrosine phosphorylation of IRS-1 in FDC cells that expressed this substrate as a result of transfection. These findings indicate that (i) IL-4, insulin, and IGF-I use signal transduction pathways in FDC lines that have at least one major feature in common, the rapid tyrosine phosphorylation of 4PS, and (ii) insulin and IGF-I stimulation of hematopoietic cell lines leads to the phosphorylation of a substrate that may be related to but is not identical to IRS-1.